Surviving the Patent Regime (The Effect on Pharma Industry) - Gupta, M. K; Mehak (Journal of Commerce and Trade, 2008)
Even after the completion of one and a half year of Patent (Amendments) Act, 2005, there has been no effect on the pharmaceutical industry in India, as was being expected. The passage of the Act was supposed to have lead to a rise in the prices of drugs in the country. This was due to the fact that once the Indian companies stopped manufacturing patented drug molecules; there would be shortage of drugs/ substitutes of drugs available in the market. Patent holding firms will have a monopoly in the market and would charge prices of drugs according to their own considerations. However, prices of most of the medicines continue to remain the same. Even the availability of the medicines has not been affected by the enactment of the law. The paper below analyses the situation that prevails in the Indian pharmaceutical industry after the implementation of the Patent (Amendments) Act, 2005.